Free-roaming dog population dynamics in Ranchi, India. (March 2022) - Evans, M.J.; Gibson, A.; Fielding, H.; Ohal, P.; Pandey, P.; Kumar, A.; Singh, S.K.; Airikkala-Otter, I.; Abela-Ridder, B.; Gamble, L.; Handel, I.; Bronsvoort, B.M.D.C.; et al.
Abstract: Rabies causes approximately 20, 000 human deaths in India each year. Nearly all of these occur following dog bites. Large-scale, high-coverage dog rabies vaccination campaigns are the cornerstone of rabies elimination strategies in both human and dog populations, although this is particularly challenging to achieve in India as a large proportion of the dog population are free-roaming and unowned. Further, little is known about free-roaming dog ecology in India which makes defining optimum vaccination strategies difficult. In this study, data collected using a mobile phone application during three annual mass vaccination and neutering (surgical sterilisation of both males and females) campaigns of free-roaming dogs in Ranchi, India (during which a total of 43, 847 vaccinations, 26, 213 neuter surgeries and 28, 172 re-sight observations were made) were interrogated, using two novel approaches to estimate the proportion of neutered dogs that were lost from the city (assumed due to mortality or migration) between campaign years. Analysis revealed high losses of neutered dogs each year, ranging from 25.3% (28.2–22.8) to 55.8% (57.0–54.6). We also estimated that the total population declined by 12.58% (9.89–15.03) over the three-year period. This demonstrates that there is a high turnover of free-roaming dogs and that despite neutering a large number of dogs in an annual sterilisation campaign, the decline in population size was modest over a three-year time period. These findings have significant implications for the planning of rabies vaccination campaigns and population management programmes as well as highlighting the need for further research into the demographics of free-roaming, unowned dogs in India. Highlights: Three canine neutering and rabies vaccination campaigns documented in Ranchi, India. Demographics of free-roaming, unowned (stray) dogs described. High losses of neutered dogs between campaigns suggesting high population turnover. Implications for efficacy of rabies vaccination campaigns and population management.